Use of GeoGebra in explorative, explanatory and demonstrative moments - Lasa, Aitzol; Wilhelmi, Miguel R. (Revista do Instituto GeoGebra Internacional de São Paulo, 2013)
The aid of this work is to present a set of GeoGebra constructions designed to study general properties over triangles, selected from Secondary Education curriculum. These constructions allow a class management centered on properties, rather than on individual examples.